The influences of attitude toward responsible fashion consumption and environmental concern on Gen Z's CSR-driven fashion brand choice intention: Empirical evidence from Germany - Henrik Vogel (IU Internationale Hochschule, 2023)
The fashion industry is considered one of the most relevant industries worldwide. At the same time, however, it is repeatedly accused of irresponsible behavior toward the environment and society. For fashion brands who identify Generation Z as an attractive customer target group, the increasing consumer sensitivity for environmental protection and corporate social responsibility (CSR) could offer promising potential for differentiation. Although this assumption is frequently cited, there has been surprisingly little research to date. In a quantitative-empirical study among n = 157 members of Generation Z in Germany, the impact, a) attitude toward responsible fashion consumption and b) environmental concern were analyzed. The results show that both, attitudes towards responsible fashion consumption and environmental concern have a positive effect on the intention to buy clothes from CSR-driven fashion brands. Furthermore, environmental concern has a reinforcing effect on the attitude-intention relationship. Recommendations for managerial practice and ideas for possible future research are derived from the results. The work is intended to contribute to a deeper understanding of the responsible fashion consumption behavior of Generation Z in Germany.
Keywords: M14; M31; L67; L81; 650; brand choice; consumer behavior; corporate social responsibility (CSR); environmental concern; fashion; Generation Z; purchase intention